Analisis Yuridis Surat Pernyataan Penguasaan Fisik Bidang Tanah (Sporadik) Atas Pemberian Tanah Secara Panjaean Pada Masyarakat Batak Toba (Studi di Desa Sibolahotang SAS dan Kantor Pertanahan Kabupaten Toba) - Rika Sandhora (Iuris Studia: Jurnal Kajian Hukum, 2021)
The custom of the Toba Batak community in the form of giving land from parents to sons which is done orally is known as Panjaean. Giving in Batak customs is a common thing in the life of the Toba Batak people. Giving (grants) orally in the Batak custom, known as Panjaean, often causes complications. Land ownership or other matters on a plot of land can be complicated, but this can be overcome by obtaining a land title certificate. This study uses the theory of legal pluralism and the theory of legal certainty. This type of research uses empirical juridical research methods that are descriptive analytical. The data sources of this research can be distinguished into primary data and secondary data. The primary data is used to obtain field research through interviews with respondents. Literature research is done by reading books, journals, and laws and regulations. The results showed that the background of giving land by parents to sons through Panjaean in the Toba Batak community in Sibolahotang Village SAS was due to the affection factor (Holong Ni Roha), the land factor as kinship identity, economic factors, and family honor factors. The status of land ownership given to sons or what is called panjaean is a property right that must be maintained and can be passed on to other descendants. The process of issuing land certificates originating from the panjaean at the Land Office requires attaching a Statement of Physical Control of Land Sector (Sporadic). because land obtained from panjaean usually does not have proof of the title because the implementation is done orally